Artificial Intelligence and Robotic surgery in Orthopaedics - Singh, Vivek (Orthopaedic Journal of M. P. Chapter, 2024)
Artificial intelligence (AI), first proposed by Prof. John McCarthy in 1956, aims to reproduce human intelligence using computers. Machine learning (ML) is a form of AI that uses computational algorithms that learn and improve with experience.[1] Artificial intelligence is improving the surgical skills of orthopaedic surgeons by improving their clinical decisions. Technology can improve the surgical skills of the doctors. It can also improve the healthcare system. By this, the computer uses neural networks and learning models to learn to distinguish patterns directly from data and learns on its own to select features to classify the input data. To put it simply, using AI and machine learning algorithms, the surgeon can make good use of a huge amount of data. This allows them to comprehend, predict, act, and learn. (2)